PENGARUH KARAKTER EKSEKUTIF, SIZE, SALES GROWTH, DAN LEVERAGE TERHADAP TAX AVOIDANCE - Deny Tristianto, 12.05.52.110; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2016)
This research aimed to examine and analyze the effect of executive characteristic, size, sales growth, and leverage towards corporate tax avoidance. The sampling technique was done by purposive sampling method. The population in this research is manufacturing companies listed on the Indonesian Stock Exchange period 2012 to 2014 with sample data which gathering of this research was 129 sample. Data was processed by SPSS software. Analysis technique using multiple regression analysis. The result of statistic t test showed that four independent variabel had a significant effect to CETR proxy of tax avoidance. Executive characteristic had a negatif significant effect to CETR, size had a positif significant effect to CETR, sales growth had a negatif significant effect to CETR, and leverage had a positif significant effect to CETR.Keywords: Executive Characteristic, Size, Sales Growth, Leverage, Tax Avoidance